2012
DOI: 10.1007/s10875-012-9706-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pro-inflammatory Cytokine Production After Lipopolysaccharide Stimulation in Patients with X-linked Agammaglobulinemia

Abstract: Our results demonstrate a predominantly inflammatory response in XLA patients after LPS stimulation and suggest a deregulation of TLR signaling in the absence of Btk. This response may be influenced by environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
4
14
0
1
Order By: Relevance
“…Finally, one study reported that Btk deficiency led to increased TLR-dependent IL12, but decreased TNF secretion in both thioglycollate-elicited peritoneal and bone marrow derived macrophages(13). Similar to the data in mice, human monocytes derived from patients lacking functional Btk have been shown to exhibit decreases(2, 14),increases(15, 16) and no change(17) in TLR-dependent pro-inflammatory cytokine secretion. Taken together, these results demonstrate that Tec kinases can positively and negatively regulate secretion of pro-inflammatory cytokines in response to TLR activation in macrophages; however, the reasons for the observed differences in polarity of their effect has not been clearly established.…”
Section: Introductionsupporting
confidence: 70%
“…Finally, one study reported that Btk deficiency led to increased TLR-dependent IL12, but decreased TNF secretion in both thioglycollate-elicited peritoneal and bone marrow derived macrophages(13). Similar to the data in mice, human monocytes derived from patients lacking functional Btk have been shown to exhibit decreases(2, 14),increases(15, 16) and no change(17) in TLR-dependent pro-inflammatory cytokine secretion. Taken together, these results demonstrate that Tec kinases can positively and negatively regulate secretion of pro-inflammatory cytokines in response to TLR activation in macrophages; however, the reasons for the observed differences in polarity of their effect has not been clearly established.…”
Section: Introductionsupporting
confidence: 70%
“…This finding supports a role for Btk in signaling via the TLR2,6 molecules. Previous data indicated that Src family kinases including c-Src regulated Btk activation [43], [44]. Therefore, activation of Btk was expected to be a consequence of c-Src activation in MALP-2-treated cells.…”
Section: Resultsmentioning
confidence: 94%
“…Btk is a non-receptor tyrosine kinase, and have been implicated in a double shift to control immune response [43]. To investigate its role in MALP-2 induced signaling, THP-1 cells were stimulated with MALP-2 for various lengths of time, and endogenous Btk was assessed for phosphorylation in the tyrosine residues at Tyr223, which was necessary for full activation of Btk [37].…”
Section: Resultsmentioning
confidence: 99%
“…T cells are felt to be functionally normal in XLA. Myeloid cells on the other hand, have had demonstrable functional deficits reported due to the role of BTK in the transduction of TLR signals [12, 13]. This has been postulated to contribute both to infection susceptibility and to a predisposition to inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%